COMPARATIVE STUDY OF BIODIESEL PRODUCTION FROM PALM OIL AND WASTE COOKING OIL USING TWO-STEPS TRANSESTERIFJCATJONPROCESS - YAACOB & SALLEH, MARWAN (2014)
Biodiesel or fatty acid methyl ester (FAME) is a renewable source of fuel which has received a great attention worldwide due to its potential to substitute petroleum based diesel. The study looking for the optimum conditions for biodiesel production which achieve at least 99% FAME purity at various reaction conditions by altering the catalyst concentration «sing two-steps alkali transesterificatioa process. The feasibility of palm oil and waste cooking oil as biodiesel feedstock was also reviewed based on both FAME purity as well as FAME yield. Preliminarv study reve^d that acceptable FAME purity and FAME yield can be obtained using lwt% KOH at 40°C reaction temperature with 1:6 oil to methanol molar ratio For one hour reaction time. At optimisation stage, four variant of catalyst concentrations in methanol were tested (0.038, 0.057, 0.087, 0.12 kg/kg) and temperature was lowered to 37°C.